2015
DOI: 10.1158/1055-9965.epi-15-0363
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Mapping of the 4q24 Locus Identifies Two Independent Loci Associated with Breast Cancer Risk

Abstract: Background A recent association study identified a common variant (rs9790517) at 4q24 to be associated with breast cancer risk. Independent association signals and potential functional variants in this locus have not been explored. Methods We conducted a fine-mapping analysis in 55,540 breast cancer cases and 51,168 controls from the Breast Cancer Association Consortium. Results Conditional analyses identified two independent association signals among women of European ancestry, represented by rs9790517 (c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Previous studies reported significant associations of variants at the TET2 locus with risk of cancer including ovarian and breast cancer (9, 21, 34). A large number of functional variants were identified in this region forming multiple pleiotropic linkage blocks that support the role of TET2 and its germline variants in the development of multiple cancer types.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies reported significant associations of variants at the TET2 locus with risk of cancer including ovarian and breast cancer (9, 21, 34). A large number of functional variants were identified in this region forming multiple pleiotropic linkage blocks that support the role of TET2 and its germline variants in the development of multiple cancer types.…”
Section: Discussionmentioning
confidence: 97%
“…A large number of functional variants were identified in this region forming multiple pleiotropic linkage blocks that support the role of TET2 and its germline variants in the development of multiple cancer types. Furthermore, an association between rs62331150 and TET2 gene expression in breast normal and tumor tissue was recently shown (9). The bidirectional association of the rs62331150 variant allele implies that the effect of TET2 genetic variation may be of a different nature for distinct cancers, increasing the risk of breast cancer, but decreasing the risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While fine‐mapping approaches are well described in the literature, it is challenging to elucidate the functional relevance of GWAS SNPs, which are predominantly from noncoding regions conferring potential gene regulatory roles. Thus far, 15 breast cancer associated GWAS variants have been fine‐mapped and characterized for putative biological roles …”
Section: Introductionmentioning
confidence: 99%